2015
DOI: 10.4067/s0718-58392015000400001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, identification, and certification of Chilean rice varieties using molecular markers

Abstract: It takes approximately 14 yr to produce a new rice (Oryza sativa L.) variety, that is, from initial hybridization to its commercial release. Currently, new varieties are identified based on morphological descriptors, which have been efficient over time. However, due to the main constraints on seed type impose to other breeding objectives and the pressure of continuous release of varieties, high degree of parentage, and genetic and morphological uniformity has been observed in the breeding populations. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…A wide range of genetic distances represented by the fixation index (F ST values) have been reported in previous studies, such as 0.87 for an elite rice genotype from Chile (Becerra et al, 2015), 0.86 for Ugandan rice (Mogga et al, 2018), and 0.01-0.76 for African rice (Ndjiondjop et al, 2018). In this study, the F ST values of wild rice with landrace, weedy, and bred rice were relatively larger compared to those among the three variety types (Figure 2C).…”
Section: Discussionmentioning
confidence: 95%
“…A wide range of genetic distances represented by the fixation index (F ST values) have been reported in previous studies, such as 0.87 for an elite rice genotype from Chile (Becerra et al, 2015), 0.86 for Ugandan rice (Mogga et al, 2018), and 0.01-0.76 for African rice (Ndjiondjop et al, 2018). In this study, the F ST values of wild rice with landrace, weedy, and bred rice were relatively larger compared to those among the three variety types (Figure 2C).…”
Section: Discussionmentioning
confidence: 95%
“…Hence with the aid of microsatellite makers and clustering data, different distantly related rice genotypes may be combined by intercrossing genotypes such as Aweil rice genotypes with IRRI rice genotypes from different clusters to get hybrid varieties with high heterosis. Many studies have also reported significantly greater allelic diversity of microsatellite markers than other molecular markers (Aguirre et al, 2005) and USA (Xu et al, 2004) and Chile (Becerra et al 2015). The narrow genetic base observed in this study is not surprising and it could be due to the fact that only a few varieties are available in the country.…”
Section: Discussionmentioning
confidence: 98%
“…The quality and quantity of rice seed is usually determined based on its various characteristics and characteristics. Classification of rice varieties in a specific area is of utmost importance to the specialists group for assessing the level of morality, as well as improving the quality of rice outside of the country [5].…”
Section: Introductionmentioning
confidence: 99%